Spectrophotometric and computational characterization of charge transfer complex of selumetinib with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone and its utilization in developing an innovative green and high throughput microwell assay for analysis of bulk form and pharmaceutical formulation - Sarah Alrubia; Wafa A. AlShehri; Awwad A. Radwan; Nourah Z. Alzoman; Ibrahim A. Darwish (BMC Chemistry)
Abstract For paediatric patients suffering from neurofibromatosis, Selumetinib (SEL) is the only approved drug. Here an original ecofriendly and high pace method is introduced using 96- microwell spectrophotometric assay (MW-SPA) to measure SEL content in bulk and commercial pharmaceutical formulation (Koselugo® capsules). This assay was relied on in-microwell formation of a coloured charge transfer complex (CTC) upon interaction of SEL with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ). The complex was fully characterized by spectrophotometric and computational studies. The CTC exhibited an absorbance maximum (λmax) at 440 nm. The ease of reaction occurrence, complex stability and its high absorptivity were proved by measuring its association constant (0.63 × 102 L/ mol), standard free energy change (-10.31 KJ/mol), molar absorptivity (ε) (3.78 × 103 L/mol/cm), and the SEL: DDQ stoichiometric ratio (1:1). Establishments of the optimum values of the applied conditions in 96-well assay plate were refined regarding DDQ concentration, reaction time, temperature, and solvents. Validation of the assay was according to the ICH guidelines. The assay was linear in SEL’ concentrations ranged from 10 to 200 µg/well, with limits of detection and quantitation of 4.1 and 12.5 µg/well, respectively. Then, the assay was efficaciously adapted to accurately and precisely determine SEL content in bulk form and Koselugo® capsules. The assay environmental safety was documented by three different comprehensive metric tools. Additionally, assessment of the assay’s rate demonstrated its high throughput, enabling the processing of large number of samples in pharmaceutical quality control laboratories. The successful development of this assay provides a valuable fast and green analytical tool for ensuring the quality control of SEL’s bulk form and capsules.